Catatan Faktor-faktor yang Mempengaruhi Pelaksanaan Supervisi Klinik oleh Manajer Perawat di Rumah Sakit - Warih Trimulyanto; Megah Andriany; Untung Sujianto (Journal of Telenursing (JOTING), 2023)
This research aims to determine Factors That Influence The Implementation Of Clinical Supervision By Nurse Managers In Hospitals. The method used is a scoping review through a review of relevant articles on topics from Google Scholar, Pubmed, Proquest and Scient Direct with the year of publication 2020 to 2023 with the keywords "Factors", â€determinantâ€, â€influencingâ€, "Supervision clinical" and "nurse managers" =. then analyzed using matrix synthesis. The inclusion criteria in this study were articles in English with a cross-sectional longitudinal study design and self-efficacy as the dependent variable. The results showed that of the 7 articles there were 5 main factors that influenced clinical supervision including supervisors and nurses' perceptions, supervisor levels or positions, supervisor knowledge and skills, workload and staff capacity. The conclusions in this study indicate that many factors can hinder the implementation of clinical supervision, but the presence of these obstacles is a key to be able to make improvements and improvements in the implementation of clinical supervision for nurses. Keywords ; Factors, Implementation, Supervision Of Clinis